Tridentate NacNac stabilized tin and nickel complexes: access to a monomeric nickel hydride and its catalytic application - Pahar, Sanjukta; Sharma, Vishal; Mahata, Biplab; George, Christy P.; Sharma, Himanshu; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2022)
The transmetalation reaction of picolyl-supported tridentate nacnac germylene monochloride [2,6-iPr2-C6H3NC-(Me)CHC(Me)NH(CH2py)]GeCl (1) (py = pyridine) with SnCl2 results in an analogous stannylene chloride (2). The three -coordinated stannylenium cation [{2,6-iPr2-C6H3NC(Me)CHC-(Me)NH(CH2py)}Sn]+ with SnCl3- as a counteranion (3) has been generated through the abstraction of chloride ligand from 2 using an additional equivalent of SnCl2. Instead of forming a donor-acceptor complex, 2 undergoes a facile redox trans-metalation reaction with Ni(COD)2 (COD = cyclooctadiene) and CuCl to afford analogous nickel and copper complexes [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]MCl [M = Ni (4) and Cu (5)]. The reactions of 4 with potassium tri-sec-butylborohydride (commonly known as K-selectride) and AgSbF6 provide access to monomeric Ni(II) hydride, [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]NiH (6) and a Ni(II) cation, [{2,6-iPr2- C6H3NC(Me)CHC(Me)NH(CH2py)}Ni][SbF6] (7), respectively. 6 was found to be an effective catalyst for the hydroboration of amides.

Tridentate NacNac tames T-shaped nickel(I) radical - Pahar, Sanjukta; Sharma, Vishal; Raj, K. Vipin; Sangole, Mayur P.; George, Christy P.; Singh, Kirandeep; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry- a european journal, 2024)
The reaction of a nickel(II) chloride complex containing a tridentate beta-diketiminato ligand with a picolyl group [2,6-iPr2-C6H3NC(Me)CHC(Me)NH(CH2py)]Ni(II)Cl (1)] with KSi(SiMe3)3 conveniently afforded a nickel(I) radical with a T-shaped geometry (2). The compound's metalloradical nature was confirmed through electron paramagnetic resonance (EPR) studies and its reaction with TEMPO, resulting in the formation of a highly unusual three-membered nickeloxaziridine complex (3). When reacted with disulfide and diselenide, the S-S and Se-Se bonds were cleaved, and a coupled product was formed through carbon atom of the pyridine-imine group. The nickel(I) radical activates dihydrogen at room temperature and atmospheric pressure to give the monomeric nickel hydride. A thermally stable, T-shaped, nickel(I) radical was straightforward obtained by reduction of a tridentate nacnac nickel(II) chloride with KSi(TMS)3. The metalloradical character of the compound was demonstrated by the formation of a highly unusual nickeloxaziridine complex upon addition of TEMPO. The Ni(I) species displays a rich chemistry towards activation S-S, and Se-Se bond leading to unusual C-C coupled product as well as dihydrogen activation at room temperature and atmospheric pressure to generate monomeric nickel hydride.+image
Keywords: C-C Bond formation; Hydrogen Activation; Metalloradical; Nickel; Tridentate nacnac